2012
DOI: 10.1111/j.1467-9299.2012.02041.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Performance Information in Budgetary Decision‐making by Legislators: Is Estonia Any Different?

Abstract: The goal of this article is to examine to what extent legislators in Estonia use performance information in budgetary decision‐making. Interviews with the members of the finance committee of the parliament show that legislators make only limited use of the formal documents containing performance information. Instead, they rely, for the most part, on informal social networks for gathering information they consider necessary for budget discussions. According to the legislators, the main reasons for limited use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
1
26

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 51 publications
9
66
1
26
Order By: Relevance
“…In general, survey-based studies that assess politicians' appreciation of performance information present 'positive' findings (Brun and Siegel, 2006;Ho, 2006). Field case studies about politicians' actual use of performance information have indicated, however, that this is minimal, or even absent (Bourdeaux, 2008;Raudla, 2012;Grossi et al, 2016). These findings seem to support the conclusion about the papers analysed in this section and the previous one.…”
Section: Performance Information Usesupporting
confidence: 81%
See 2 more Smart Citations
“…In general, survey-based studies that assess politicians' appreciation of performance information present 'positive' findings (Brun and Siegel, 2006;Ho, 2006). Field case studies about politicians' actual use of performance information have indicated, however, that this is minimal, or even absent (Bourdeaux, 2008;Raudla, 2012;Grossi et al, 2016). These findings seem to support the conclusion about the papers analysed in this section and the previous one.…”
Section: Performance Information Usesupporting
confidence: 81%
“…There is, however, a lack of consensus in the findings. Low levels of appreciation and use are found in studies conducted at the central government level in the UK (Johnson and Talbot, 2007); at the state level (Bourdeaux, 2008) and the federal level (Stalebrink and Frisco, 2011) in the USA; in Estonia's central government (Raudla, 2012); in Dutch municipalities (ter Bogt, 2004); and in German and Italian local governments (Grossi et al, 2016). Other studies, however, show opposite, more 'positive' findings, especially Askim (2007) for Norwegian municipalities; Brun and Siegel (2006) for the Swiss central and intermediate governments; Saliterer and Korac (2013) for municipalities in Austria; and Ho (2006) for local governments in the USA's midwest.…”
Section: Overview Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for PI depends on the goals, interests and institutional logics incorporated in the particular hybrid and in its stakeholderssee Høgvold Olsen et al (2017). While some stakeholders use PI in a functional way, as in other types of organizations there are also variants of a more symbolic or 'political' use of PI (Raudla, 2012; see also Agostino and Arnaboldi, 2017, on p. 409 of this issue). Politicians, for instance on SOE boards, are often quite reluctant to use such data (except perhaps opposition politicians using PI for blame-shifting), because they fear that such data might help their political enemies.…”
Section: Performance Of Hybrid Organizationsmentioning
confidence: 99%
“…If legislators trust the entity that provides the analysis (Bourdeaux 2008;Raudla 2012), and if the information benefits the odds of their reelection and fuels their desire to play an active role in the policy-making process, those legislators will be more open to legislative advocacy. In such cases they are likely to be influenced by CSO opinions.…”
Section: Theory and Hypothesesmentioning
confidence: 99%